DETERMINATION OF BENEFICIAL COMPOUND FROM PITHECELLOBIUM JIRINGA (JERING) SEED EXTRACTED USING ULTRASONIC EXTRACTION METHOD - ZULKFLE, MUHAMMAD NUR HIDAYAT (IRC, 2019)
Recent researches have shown that Pithecellobium Jiringa seeds help in cancer prevention and treatment due to rich, active antioxidants mainly phenolic and flavonoid compounds presence in the seeds that act as anticancer agent. However, prevailed cases regarding consumption of Pithecellobium Jiringa seeds in a lot of quantity have been commented as a dangerous toward the consumers health as the seeds contain djenkolic acid. Therefore, this study proposed the proper method of extracting the bioactive compounds contained in Pithecellobium Jiringa seeds using ultrasonic extraction method in the aspect of maximizing yield of extracts, Total Phenolic Content (TPC) and Total Flavonoid Content (TFC). Study pertaining sample mean particle size was also included due to its high effects on the extraction rate and yield of the bioactive compounds. The mean particle size studied were 0.5, 0.71 and 1.0 mm. Solid to solvent ratio was as well studied due to the lack of researches related to this aspect despite of its critical effects in extracting the content of the seeds. Solid to solvent ratio examined were 1:10, 1:20 and 1:30 in g/ml.